FIRM-SPECIFIC DETERMINANTS OF FIRM VALUE IN NON-CYCLICALS CONSUMER SECTOR COMPANIES - Salim, Sharolyn Handayani; Radianto, Wirawan Endro Dwi (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study aims to investigate the effect of profitability level, investment decision, and firm age on firm value. Research Methods. The research method used quantitative method using secondary data sources, which is the annual report of consumer non-cyclicals sector registered in the Indonesia Stock Exchange (IDX) for 2020-2022. The data processed 125 companies and the sampling process was purposive sampling, so the sample obtained 65 companies with total of 195 data observation. Research Results and Findings. This research provides evidence that profitability level, investment decision, and firm age affect firm value. This study has important value in helping companies develop effective business strategies amid economic uncertainty and provide insight for investors to make wiser investment decisions in this sector during the crisis.